Penerapan Etika Bisnis Islam dalam Pelayanan Biro Travel Umroh dan Haji di Kabupaten Jombang - Ainun Nur Fitria, Ika; Widyaningsih, Bekti; Ni'mati Rahmawati, Arivatu (Journal of Islamic Economics Studies and Practices, 2024)
This research explores Islamic business ethics in Umrah and Hajj travel agency services in Jombang Regency. This research aims to find out whether this travel agency has implemented Islamic business ethics in its Umrah and Hajj travel agency services, to explain the values of Islamic business ethics in its services to Umrah and Hajj travel, to explain the congregation's interest in Umrah and Hajj travel, supporting factors and inhibiting factors. in Umrah and Hajj travel agency services. The research analysis used is a descriptive qualitative approach which aims to determine the circumstances and conditions, the results of which are presented in the form of a research report. The method applied is the principles of Islamic business ethics in the form of Siddiq, Amanah, Tabligh, Fathanah. This research concluded that the Umrah and Hajj travel agencies in Jombang Regency have implemented Islamic business ethics and complied with Islamic law. The values that have been implemented are in accordance with what the Prophet implemented, namely honesty, justice, responsibility, and not bad-mouthing other people's business. The congregation's interest in registering with the travel agency in Jombang Regency is quite high due to several internal and external factors.